THE IMPORTANCE OF MEDICAL SCIENCE IN CHRISTIAN MONASTERIES OF THE 18TH - 19TH CENTURIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
State-church relations are one of the key components of the domestic and foreign policy of any state as a set of historically developing and changing forms of interdependence between state institutions and religious organizations. Historically, For the Russian people there is a close connection between Orthodoxy and nationalism. At the beginning of the twentieth century, the role of the Russian Orthodox Church (ROC) in the economic and social life of the country was great.